Circulating CD14brightCD16+ 'intermediate' monocytes exhibit enhanced parasite pattern recognition in human helminth infection. - Joseph D Turner; Claire D Bourke; Lynn Meurs; Moustapha Mbow; Tandakha Ndiaye Dièye; Souleymane Mboup; Katja Polman; Adrian P Mountford (Public Library of Science (PLoS), 2014)
Circulating monocyte sub-sets have recently emerged as mediators of divergent immune functions during infectious disease but their role in helminth infection has not been investigated. In this study we evaluated whether 'classical' (CD14brightCD16-), 'intermediate' (CD14brightCD16+), and 'non-classical' (CD14dimCD16+) monocyte sub-sets from peripheral blood mononuclear cells varied in both abundance and ability to bind antigenic material amongst individuals living in a region of Northern Senegal which is co-endemic for Schistosoma mansoni and S. haematobium. Monocyte recognition of excretory/secretory (E/S) products released by skin-invasive cercariae, or eggs, of S. mansoni was assessed by flow cytometry and compared between S. mansoni mono-infected, S. mansoni and S. haematobium co-infected, and uninfected participants. Each of the three monocyte sub-sets in the different infection groups bound schistosome E/S material. However, 'intermediate' CD14brightCD16+ monocytes had a significantly enhanced ability to bind cercarial and egg E/S. Moreover, this elevation of ligand binding was particularly evident in co-infected participants. This is the first demonstration of modulated parasite pattern recognition in CD14brightCD16+ intermediate monocytes during helminth infection, which may have functional consequences for the ability of infected individuals to respond immunologically to infection.